Integrating Health Services in Ontario Through Mergers and Centralization - Krithika Ragupathi (McMaster University Library Press, 2020)
On 18 April 2019, the Legislative Assembly of Ontario passed Bill 74, The People's Health Care Act, which provided new authorities to the Ministry of Health and a newly createdOntario Health super agency to facilitate the integration of health care services across Ontario. This reform represents a shift away from the previous regionalized system of Local Health Integration Networks (LHINs). While centralization is intended to improve efficiency within the system and create a patient-centred model of care, it also equips the Ministry and Ontario Health with greater authority over health agencies. Ontario's reform represents another move towards centralization in a wave of regionalization reversal that has swept across the country. Implementation of this reform will take several years to roll out. An analysis of centralization reforms in other jurisdictions can provide insight into Ontario's decision to reform. Though this bill was presented as a modernization of Ontario's health system to meet people's needs, a common theme in stakeholders' opinions is the lack of consultation with the public.